Micro Power 14-bit A/D Converter : 45 uW At± 1.25 V and 16 K samples/s - Grisoni, L.; Heubi, Alexandre; Balsiger, Peter; Pellandini, Fausto (My University, 1997)
Micro power converters are required for power sensitive, battery-operated devices. Keeping thisgoal in mind IMT first developed a RSD cyclic converter featuring 13 bits of dynamic range and 60 dB ofSNR. The relative precision behavior is due to technology limitations (capacitor mismatch, finite DC gain ofOTA). However, digital correction is possible and this paper presents the implementation in a low voltage 1µm CMOS technology of a new linear ADC. The targeted performances were 14 bits and 45 µW @ 16 kHz& ±1.25 V power supply for a die size of 1.17 mm2. “Layout level” simulations however showed that to reachthe 14 bits, a power supply of ±1.5 V is required and results in a 65 W power consumption.